PENGARUH EKONOMI RUMAH TANGGA TERHADAP SIKAP REMAJA ATAS PENDEWASAAN USIA PERKAWINAN DIKENAGARIAN SUNGAI PINANG KECAMATAN RANAH AMPEK HULU TAPAN KABUPATEN PESISIR SELATAN - Atika Putri Azura; Khairani Khairani (JURUSAN GEOGRAFI FIS UNP, 2020)
This research was conducted with the aim to determine the effect of household economics on adolescent attitudes towards maturity of the age of Dikenagarian Sungai Pinang in terms of the indicators of each variable. this type of research is correlation that uses a quantitative approach. The sample used was 53 adolescents in Pinang river. The selection of samples using porposive sampling with adolescents as the object of the study. The data collection technique is observation to each of the teenage houses in the pinang river, and also using questionnaires. Based on the results of research using simple linear regression data analysis techniques Y = 22,650 + 0.563 X. There is a significant (significant) influence on the household economy on attitudes towards maturing marriage age. The better the economic situation of adolescent households tends to mature the age of marriage, the more understanding and more mature marriage age. And vice versa, the weaker household economy tends not to prioritize the age of marriage.